Metagenomic insights into the effect of thermal hydrolysis pre-treatment on microbial community of an anaerobic digestion system - Zhang, Liang (2022)
Thermal hydrolysis process (THP) is an effective pre-treatment method to reduce solids volume and improve biogas production during anaerobic digestion (AD) via increasing the biodegradability of waste activated sludge (WAS). However, the effects of THP pre-treated sludge on microbial diversity, interspecies interactions, and metabolism in AD systems remain largely unknown. We therefore setup and operated an anaerobic digester during a long-term period to shed light on the effect of THP pre-treatment on AD microbial ecology in comparison to conventional AD via Illumina based 16S rRNA gene amplicon sequencing and genome-centric metagenomics analysis. Results showed THP sludge significantly reduced the microbial diversity, shaped the microbial community structure, and resulted in more intense microbial interactions. Compared to WAS as the feed sludge, THP sludge shaped the core functional groups, but functional redundancy ensured the system's stability. The metabolic interactions between methanogens and syntrophic bacteria as well as the specific metabolic pathways were further elucidated. Hydrogenotrophic methanogens, Methanospirillum sp. and Methanolinea sp., were the primary contributors for methane production when treating THP and WAS, respectively, which also have potential for acetate oxidation to methane. Collectively, this study provides in-depth information on the interspecies interactions to better understand how THP pre-treatment influences AD microbial community.